Aquatic and hygrophilous plants of ponds in the "Riserva Naturale di Cornocchia" and "La Selva" (catchment area of the river Feccia, Tuscany) [Le piante acquatiche e igrofile negli stagni della Riserva Naturale di Cornocchia e del complesso demaniale “La Selva” (Bacino del fiume Feccia, Toscana)] - Landi, Marco; Saveri, Carlo; Frignani, Flavio; Angiolini, Claudia (2012)
In this paper, we present the richness and composition of aquatic (hydrophytes) and hygrophilous species of 37 artificial ponds, located in forest and grassland pastures within a protected area of Tuscany (central italy). after about 50 years from their creation, they have shown a high frequency of these species and the presence of interesting plants as Alisma lanceolatum, Groenlandia densa, Juncus bulbosus, Potamogeton trichoides and Zannichellia palustris. The hydrophytic and hygrophilous exotic species are absent. The ponds are habitat of Community interest “Codice 3140” - Hard oligo-mesotrophic waters with benthic vegetation of Chara spp.” for the frequency of occurrence of Chara hispida, meso-oligotrophic species and chemical characteristics.